PERAN PROMOSI DAN LOKASI DALAM MENINGKATKAN PENJUALAN UNIT PERUMAHAN PURI DELTA ANGSANA DI KECAMATAN KASEMEN KOTA SERANG - Abdul Aziz; Sahrul Arixona (Universitas Bina Bangsa, 2021)
The purpose of this study was to determine whether there is a partial and simultaneous influence on promotion and location in increasing sales of Puri Delta Angsana housing units in Kasemen District. The research method used is quantitative research methods. The research population is Puri Delta Angsana Housing in Kasemen District, Serang City which was recorded in 2021 as many as 72 housing units. The data analysis techniques used by researchers include descriptive statistics, validity tests, reliability tests, classical assumption tests, multiple linear regression tests, correlation coefficient tests, test determination, T test, and F test. The results of this study indicate that promotion partially has a significant effect on sales, the tcount value is 2.894 > ttable value is 1.666, the significant value is 0.004 <0.05. Location partially has a significant effect on sales, tcount value is 3,248> ttable is 1,666, significant value is 0.005 <0.05. Promotion (X1), and Location (X2) together (simultaneously) have a significant effect on Sales (Y) at Puri Delta Angsana Housing in Kasemen District, Serang City with a significant value of 0.000b < 0.05 and an F value of 16.664 > 3 ,13. The coefficient of determination (R Square) obtained is 0.326. This means that 32.6% of the sales variation can be explained by the Promotion and Location variables. While the remaining 67.4% is influenced by other variables not included in the study